Effect of proinflammatory cytokines on lung and intestinal mucosal permeability in vitro - Alshehri, Abdullah Ali (2013)
Transport of therapeutics across mucosal barriers provides an attractive route for non-invasive drug delivery, if sufficient drug permeability can be achieved. In inflammatory conditions of the epithelial mucosa, the barrier characteristics were observed to be modified with the permeability of noxious molecules increased significantly due to, at least in part, elevated levels of proinflammatory cytokines leading to tight junction disruption. This work aims to investigate the effect of selected cytokines on the barrier characteristics of airway and intestinal cell cultures in vitro in order to improve the understanding of transport features across inflamed epithelial cell layers. Data indicated that a three-four days short-term treatment with tumor necrosis factors-alpha (TNF-α) produced a significant effect on Calu-3 cell layers and some effect on Caco-2 cells, as shown by decreased transepithelial resistance (TEER values and increased permeability of model permeant (fluorescein isothiocyanate dextran with molecular weight of 10kDa, FD10). On the other hand, short-term treatments with proinflammatory cytokines interleukin-4 and interleukin-13 IL-4 and IL-13 did not show significant effects on the tested cell lines. Combined effect of cytokines was shown to cause a significant effect on Calu-3 apparent permeability coefficient (Papp) when the combination contains TNF-α, while the Papp across Caco-2 layers was observed to be influenced by IL-4/IL-13 combination; the effect being reduced when TNF-α was present. In the situation of long-term treatment (for the duration of cell culture), IL-4 and IL-13 did not produce a significant effect on TEER and Papp for both cell lines when incubated for 21 days. TNF-α however produced a significant effect on FD10 permeability across layers of both cell lines. Finally, the work examined the expression features of tight junction proteins (TJP2 and TJP3) and endocytosis pathway components (LAMP1, RAB4A, and RAB5A) in the cell layers following a prolonged exposure to the proinflammatory mediator TNF-α. Results demonstrated that expression of the tested TJ proteins was downregulated, though endocytosis related proteins did not show alteration in their expression. These results therefore indicated that the presence of proinflammatory cytokines could be involved in the improvement in the transport of macromolecules through epithelial mucosa by affecting a TJ opening.